MODERN USE OF DRUGS IN BRONCHOPULMONARY PATHOLOGY - Abdumavljanovna Azizova, Rihsi; Abdulazizovna Valieva, Tamila (PT. Antis International Publisher, 2024)
Objective: This study aims to evaluate the rational pharmacotherapy for bronchopulmonary diseases in children with recurrent bronchitis, focusing on treatment effectiveness and safety. Methods: A retrospective analysis of 28 children aged 1.5 to 10 years, diagnosed with acute bronchitis, recurrent bronchitis, and pneumonia, was conducted. The patients were treated at a pulmonology department and underwent clinical, laboratory, and radiological assessments. Treatment regimens included third-generation cephalosporins, glucocorticoids, and antihistamines, administered according to age-based standards. Results: The study revealed that all patients exhibited moderate symptoms upon admission, with many presenting coexisting conditions such as chronic ENT diseases and iron-deficiency anemia. Clinical laboratory tests indicated iron deficiency anemia and mild leukocytosis across all groups, suggesting impaired oxygen delivery and ongoing inflammation. The pharmacotherapy was generally well-tolerated, with notable improvements in respiratory function and recovery in most children. Novelty: This study highlights the importance of personalized pharmacotherapy in managing recurrent bronchitis in children, particularly considering comorbid conditions. It emphasizes the role of comprehensive treatment protocols integrating antibiotics, glucocorticoids, and antihistamines for effective management.